2011
DOI: 10.1007/s10545-011-9283-y
|View full text |Cite
|
Sign up to set email alerts
|

Mild hyperphenylalaninemia: to treat or not to treat

Abstract: One of the issues to be resolved in phenylketonuria is whether patients with mild hyperphenylalaninemia need treatment, or in other words, in what patients treatment needs to be started. Do patients need treatment when phenylalanine concentrations in blood are >360 μmol/L or >600 μmol/L? This paper reviews the literature on the outcome of untreated patients with mild hyperphenylalaninemia to try to determine whether outcome is normal. The paper concludes that there is, in fact, only one paper that can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 52 publications
(80 reference statements)
0
23
0
Order By: Relevance
“…In addition, despite our intentions to orient participants towards collective interests, an individualist mindset prevailed. Finally, the impact of over‐diagnosis and other complex screening biases is not well understood in the context of NBS so were not considered in this study.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, despite our intentions to orient participants towards collective interests, an individualist mindset prevailed. Finally, the impact of over‐diagnosis and other complex screening biases is not well understood in the context of NBS so were not considered in this study.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, the safe target value for serum phenylalanine has been lowered since the 1960s, driving an increase in the proportion of hyperphenylalaninemia patients requiring ongoing follow up. 31,32 Treatment of MHP through a phenylalanine-free diet and monitoring may prevent intellectual disability but also carries lifelong social and physical costs. 33 Medication-based approaches (sapropterin dihydrochloride) may cost families up to US$129,800 per annum in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Despite phenylalanine levels of 200-600 µmol/L (two to six times the normal range) this variant has, in several studies, shown to be benign (Smith et al, 2000;Weglage et al, 2001). However, this premise has recently come under question (van Spronsen, 2011). The prevalence in Taiwan is 52% (Niu et al, 2010), double that of most jurisdictions.…”
Section: Non-pku Mild Hyperphenylalaninemia (Mhp)mentioning
confidence: 99%